Análise da sustentabilidade da produção orgânica do município de Guaraciaba do Norte, Ceará: Um estudo de caso - Serafim, Cláudio Hugo Moreira (2007)
This work had live objective analyse the sustentability of organic products of Guaraciaba do Norte City, doperving the case of organic farming for Development Association. Considering the theoric basis of this academic work, was used “Diamante de Porter” model, for adapting the challenge to measure the sustentability index. The theoric Model of “Diamante de Porter” analyzes the sustentability considering its qualitative aspect, retracting the existence of four fundamental interconnected determinations: Factors conditions (DI), Demand conditions (D2), Correlated Industries and Support (D3) and Structures, strategies adn Internal Rivalship (D4). This model also contains other two determined auxiliaries that have their elements and these are characterized influencing and leeing influenced by the fundamental determinations: The Government Responsibility (D5) and the Hazard (D6). Each one of these determinations tries to avaliate considering the quantity of their elements with indicators of Van Duren el alli (1993) that vary of -2 (much favourable) to +2 (much infavourable) with intermediate unitarian values that vary progressively live “infavourable”, “imparcial” and “favourable”. Like instrument for collecting informations was used Participative Workshop, using a techinic called “Diagrama de Ishikawa”, also known as “jishbone”, that means a general problem avaliation, its motives and origin. The mistake can be produced under failure inthe brainstorm process, a phase of the diagram. This Workshop took place in Agricultural Economy Department of Ceará Federal University at 30 november 2006, with all the “Key-agents” of the organic productive chain. Among them, were present the imput distributor, productors, associated people and ADAO management, and also representative of government institutions, like EMBRAPA Researchers, an agricultural engineer of BANCO DO NORDESTE (BNB) and an agent of Supportable Development of Brazil Bank. According to the Workshop's result, the organic production in Guaraciaba do Norte was measured and scored a rate of 0,694, being in the “neutrality's group”. In the other words it's between 0 and +1, showing that the city's organic production's sustainability can be affected by determinatings and underfactores analyzed by the Porter's Diamond, besides some of these elements compromisses the organic area's growth. The results also indicated that Correlated Industries and “of Support”, got the highest relative net, showing that the imput sector is a connection of the chain that needs support to private technical assistance and about gouvernment aspect, the certification for its long period and the expenses were difficulties that contributed for a much “unfavourable avaliation”. In the factores conditions, the soil was avaliated by chain agents as an element with a best avaliation so quantitative as qualitative, in the reason of biological treatment. About the strategies used by the association, the “AMC System” integrated só much more the consumer and promoted his confidence in consuming ADAO products. So we can conclude that among all of the determinations analyzed, productors and associated people are strengthened by “AMC System”, created for the own association. It's necessary more public and qualified technical assistance for working with organic productors of Guaraciaba do Norte.